Bowling loads and injury risk in male first class county cricket: Is 'differential load' an alternative to the acute-to-chronic workload ratio?. Issue 6 (June 2020) - Tysoe, Alexander; Moore, Isabel S.; Ranson, Craig; McCaig, Steve; Williams, Sean
Abstract: Objectives: Methodological concerns relating to acute-to-chronic workload ratios (ACWR) have been raised. This study aimed to assess the relationship between an alternative predictor variable named 'differential load', representing the smoothed week-to-week rate change in load, and injury risk in first class county cricket (FCCC) fast bowlers. Design: Prospective cohort study. Methods: Bowling loads and injuries were recorded for 49 professional male fast bowlers from six FCCC teams. A range of differential loads and ACWRs were calculated and subjected to a variable selection procedure. Results: Exponentially-weighted 7-day differential load, 9:21-day ACWR, 42-day chronic load, and 9-day acute load were the best-fitting predictor variables in their respective categories. From these, a generalized linear mixed-effects model combining 7-day differential load, 42-day chronic load, and 9-day acute load provided the best model fit. A two-standard deviation (2SD) increase in 7-day differential load (22 overs) was associated with a substantial increase in injury risk (risk ratio [RR] = 2.47, 90% CI: 1.27–4.80, most likely harmful ), and a 2SD increase in 42-day chronic load (17.5 overs/week) was associated with a most likely harmful increase in injury risk (RR = 6.77, 90% CI: 2.15–21.33). For 9-day acute load, very low values (≤1 over/week) were associated with a most likely higher risk of injury versus moderate (17.5 overs/week; RR: 15.50, 90% CI: 6.19–38.79) and very high 9-day acute loads (45.5 overs/week; RR: 133.33, 90% CI: 25.26–703.81). Conclusions: Differential loads may be used to identify potentially harmful spikes in load, whilst mitigating methodological issues associated with ACWRs.